Multilinear Singular Integral Operators on Generalized Weighted Morrey Spaces - Yue Hu; Zhang Li; Yueshan Wang (Journal of Function Spaces)
The purpose of this paper is to discuss the boundedness properties of multilinear Calderón-Zygmund operator and its commutator on the generalized weighted Morrey spaces.